Brazilian Thoracic Society recommendations for the diagnosis and treatment of chronic thromboembolic pulmonary hypertension - Fernandes,Caio Julio Cesar dos Santos (2020)
ABSTRACT Chronic thromboembolic pulmonary hypertension (CTEPH) is a serious and debilitating disease caused by occlusion of the pulmonary arterial bed by hematic emboli and by the resulting fibrous material. Such occlusion increases vascular resistance and, consequently, the pressure in the region of the pulmonary artery, which is the definition of pulmonary hypertension. The increased load imposed on the right ventricle leads to its progressive dysfunction and, finally, to death. However, CTEPH has a highly significant feature that distinguishes it from other forms of pulmonary hypertension: the fact that it can be cured through treatment with pulmonary thromboendarterectomy. Therefore, the primary objective of the management of CTEPH should be the assessment of patient fitness for surgery at a referral center, given that not all patients are good candidates. For the patients who are not good candidates for pulmonary thromboendarterectomy, the viable therapeutic alternatives include pulmonary artery angioplasty and pharmacological treatment. In these recommendations, the pathophysiological bases for the onset of CTEPH, such as acute pulmonary embolism and the clinical condition of the patient, will be discussed, as will the diagnostic algorithm to be followed and the therapeutic alternatives currently available.